TEACHER COMMUNICATION SKILLS - Shamsutinova Nazokatxon; Qodirova Mohlaroyim Ravshanbek qizi (TADQIQOTLAR, 2025)
Annotation:This  article  explores  the  significance  of  teacher  communication skills in the educational process. It discusses various forms of communication used by teachers,  their  impact  on  student  learning,  classroom  environment,  and  the development  of  teacher-student  relationships.  The  article  also  highlights  the  key communication competencies every teacher should master, along with challenges and improvement strategies.